What does the pharmacological future of treating chronic hepatitis C look like?. Issue 5 (September 2015) - Heil, Emily L; Hynicka, Lauren M; Kottilil, Shyam; Tang, Lydia
<x xml:space="preserve">Abstract</x> Development of direct acting antivirals has revolutionized the standard of care for the treatment of hepatitis C virus. New interferon-free regimens provide sustained virologic response rates of >90% in many genotype 1 patients with only 12 weeks of oral therapy. This review will provide a brief overview of current standards of care with a summary of the evidence supporting the recommended combinations of direct acting antivirals. We will discuss the direction of future therapies, with strategies for shorter durations of therapy and new all-oral combinations in the pipeline.